Peningkatan Kompetensi Sdm Umkm Melalui Pelatihan Manajemen Kinerja - Bambang Kurnia Nugraha; Ridwan Hakiki (CV. SINAR HOWUHOWU, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving local economic development, including in Puteran Village, Pagerageung Subdistrict, Tasikmalaya Regency. However, many MSME actors in this area still face challenges related to human resource quality, particularly in performance management. Identified problems include the absence of systematic performance management practices, unclear performance indicators, and limited understanding of the importance of performance evaluation. This Community Service Student Creativity Program (PKM-PM) aims to enhance MSME human resource competencies through structured and practical performance management training. The implementation method includes identifying the needs of MSME partners in Puteran Village, developing training modules, conducting participatory training sessions, and providing post-training assistance and evaluation. The training materials cover goal setting, development of simple performance indicators, performance evaluation, and feedback mechanisms. The results indicate improved understanding of performance management concepts and positive changes toward more directed and measurable work practices. This program is expected to increase productivity and support the sustainability of MSMEs in Puteran Village.